The first-time manager - Belker, Loren B. (AMACOM, 2005)
A true management classic with 200,000 copies sold!
Includes index.
Keywords: Supervision of employees.; Office management.; Personnel -- Supervision.; Bureaux -- Organisation.; BUSINESS & ECONOMICS -- Workplace Culture.; BUSINESS & ECONOMICS -- Human Resources & Personnel Management.; Office management; Supervision of employees